Pelatihan Ultanum Sebagai Media Pembelajaran Matematika di Sekolah Dasar - Lisa Virdinarti Putra; Sri Mujiyono; Ela Suryani (Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of the community service program is to provide online learning model training in mathematics subjects using the numeracy snake and ladder game application at SDN Susukan 04. This community service utilizes Android as a learning medium in elementary mathematics numeracy with the aim of honing students' numeracy literacy. The data from this service were obtained through interviews with the homeroom teacher who became the main source, observations in the form of passive participation observations and documentation as supporting data from the results of the interviews. The results of the service show that teachers have used ultanum media as a learning medium in supporting online learning activities for mathematics subjects to be able to hone students' numeracy literacy. The implementation of the use of ultanum media as a learning medium has several obstacles, namely signal interference, the level of mathematical literacy is still at levels 1-3, but the benefits obtained from this service include being able to hone the ability of teachers to develop numeracy skills at levels 1-3, problem solving skill in doing mathematics learning with ultanum games and honing their skills in numeracy literacy.